The history and future trends of ocean warming-induced gas hydrate dissociation in the SW Barents Sea - Vadakkepuliyambatta, Sunil; Chand, Shyam; Bünz, Stefan (Geophysical Research Letters, 2017)
Source at https://doi.org/10.1002/2016GL071841 . The Barents Sea is a major part of the Arctic where the Gulf Stream mixes with the cold Arctic waters. Late Cenozoic uplift and glacial erosion have resulted in hydrocarbon leakage from reservoirs, evolution of fluid flow systems, shallow gas accumulations, and hydrate formation throughout the Barents Sea. Here we integrate seismic data observations of gas hydrate accumulations along with gas hydrate stability modeling to analyze the impact of warming ocean waters in the recent past and future (1960–2060). Seismic observations of bottom‐simulating reflectors (BSRs) indicate significant thermogenic gas input into the hydrate stability zone throughout the SW Barents Sea. The distribution of BSR is controlled primarily by fluid flow focusing features, such as gas chimneys and faults. Warming ocean bottom temperatures over the recent past and in future (1960–2060) can result in hydrate dissociation over an area covering 0.03–38% of the SW Barents Sea.